2002
DOI: 10.1046/j.1525-142x.2002.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancient ontogenies: larval development of the Lower Cretaceous anuran Shomronella jordanica (Amphibia: Pipoidea)

Abstract: The Lower Cretaceous anuran Shomronella jordanica (Pipoidea) is represented by an assemblage of nearly 300 tadpoles of different ages. The size of the assemblage allows a reconstruction of the larval ontogeny of this species. We describe the ossification sequence and growth rates of S. jordanica and present reconstructions of tadpoles at different stages. The ontogeny of the species seems to be similar to that of extant pipids in many aspects. Larvae are similar in shape and size to those of Xenopus laevis but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Onset of ossification is evident at Stages 52–54 ( Figure 1, I, J ). Prior reports suggested that the parasphenoid ossified soon after;[15], [23] however, we found that the otic capsules and axial column were the next to ossify. Based on our μCTs, parashenoid ossification was not evident until stage 59 ( Figure 2, G′ ).…”
Section: Resultscontrasting
confidence: 69%
“…Onset of ossification is evident at Stages 52–54 ( Figure 1, I, J ). Prior reports suggested that the parasphenoid ossified soon after;[15], [23] however, we found that the otic capsules and axial column were the next to ossify. Based on our μCTs, parashenoid ossification was not evident until stage 59 ( Figure 2, G′ ).…”
Section: Resultscontrasting
confidence: 69%
“…Despite the high abundance of specimens, the Libros tadpoles represent only certain developmental stages (Gosner stages 30–41). A bias towards specific developmental stages has been noted in other exceptionally preserved larval anuran faunas (Chipman & Tchernov 2002; Maus & Wuttke 2002; Roček 2003); tadpoles from Enspel (Maus & Wuttke 2002) exhibit bias towards developmental stages similar to that of the Libros specimens. Both the earliest (embryos and hatchlings) and metamorphic developmental stages are absent in the Libros material.…”
Section: Ecologymentioning
confidence: 69%
“…, 2004), and that the condition seen in pipoids and some microhylids, which have simpler larval jaws (Orton, 1957; Starrett, 1973) is derived, rather than primitive. Fossil larvae, known as early as the Lower Cretaceous (Chipman & Tchernov, 2002), already exhibit the general form of modern tadpoles (Fig. 26).…”
Section: Features Distinguishing Salamanders Frogs and Caeciliansmentioning
confidence: 99%
“… Two larval stages of the Lower Jurassic pipoidea frog Shomronella jordanica from the Lower Cretaceous. Reproduced from Chipman & Tchernov (2002). …”
Section: Features Distinguishing Salamanders Frogs and Caeciliansmentioning
confidence: 99%